Highly active pandanus nanocellulose-supported poly(amidoxime) copper (II) complex for Ullmann cross-coupling reaction - Choong, Jian Fui; Tang, Xin Ting; Mohd Sani Sarjadi; Md Lutfor Rahman (MDPI, 2020)
The transition metal-catalyzed chemical transformation of organic electrophiles, and organometallic reagents have turned up as an exceedingly robust synthetic tool. The evolution of transition metal catalysts has attained a stage of civilization that authorizes for an extensive scope of chemical bonds formation partners to be combined efficiently. The applications of Cu-based nanoparticles have received great attention owing to the earth-abundant, low toxicity and inexpensive. Due to these characteristics, copper nanoparticles have generated a great deal of interest especially in the field of catalysis. In this study, poly(acrylonitrile) was synthesized by undergoes free-radical initiation process and followed by Beckmann rearrangement with hydroxylamine solution converted into the poly(amidoxime) ligand and anchored the copper onto poly(amidoxime). Cu(II)@PAM was characterized using different techniques such as FTIR, FESEM, EDX, TEM, TGA, DSC, ICP-OES, and XPS analyses. The Cu(II)@PAM showed high stability and high catalytic activity in a wide variety of electrophilic substituted phenols with substituted aryl/benzyl halides. 0.15 mol%, ±3 mg of Cu(II)@PAM could efficiently promote Ullmann reaction to give the corresponding coupling product up to 99 % yields. The complex was easy separated and recovered from the reaction mixture by simple filtration.